Evaluation of OrthoChromic OC-1 films for photon radiotherapy application. (1st December 2022) - Lim, Seng Boh; Tang, Grace
Abstract: A new film dosimetry system consists of the new OrthoChromic™ OC-1 film, and a novel calibration procedure was evaluated. Two films, C1 and C2, were exposed simultaneously using the 6FFF beam with a step-wedge pattern of five steps ranging from 590 to 3000 cGy. C1 was used for calibration, and C2 was used for calibration curve validation. The second scan of C2 was done by rotating the film by 90-deg. To evaluate the effectiveness of the non-uniform scanner response correction with the new system, a film was exposed to a 20 × 20 cm 2 field. The beam profile measured with the film was compared to the IBA cc04 measurements in water. Films were irradiated to characterize the energy response, dynamic range and temporal growth effect. Open (MLC-defined) and clinical fields were radiated to evaluate the overall performance of the new system. The new calibration procedure was validated with an average dose difference of 1.6% and a gamma (2%, 2 mm) passing rate of 100%. With C2 scanned 90-deg rotated, the average dose difference was 1.3%. The average difference between cc04 and film was 0.4%. The St between films and diode/cc04 were within −0.3% difference for 1 × 1 to 14 × 14 cm 2 and −2.8% for 0.5 × 0.5 cm 2 . For clinical fields, the average gamma (3%, 2 mm) was 98.8%. These results were consistent with EBT3 film and MapCheck measurements with a dose > 400 cGy. The results have shown that the OC-1 film system can achieve accurate results for QA measurements, but more considerable uncertainty was observed within the low dose range.